Transformation of the Meaning of Njalang Tradition: From a Personal Ritual to a Medium of Preservation and Cultural Tourism Among the Nasal Clan in Bengkulu - Andriyanto, Andriyanto; Hadiprashada, Dhanurseto; Firmansyah, Mas Agus (Universitas Pattimura, 2024)
This study examines the transformation of the Njalang tradition among the Nasal clan in Kaur Regency, Bengkulu, from a personal spiritual ritual into a collective cultural event. Once limited to individual visits during Eid al-Fitr, Njalang has evolved into a structured mass pilgrimage involving pre-event meetings, communal services, and ceremonial activities on the second day of Shawwal. Using an ethnographic communication approach, the research involved direct participation and observation to interpret the evolving meanings of this tradition. Findings reveal that Njalang now functions not only as a spiritual practice but also as a means of strengthening social ties, preserving cultural identity, and promoting cultural tourism. This transformation illustrates how local traditions adapt to contemporary contexts while retaining core communal values. The study’s novelty lies in its focus on the transformation of meaning—an aspect often overlooked in previous research. It highlights how traditional rituals can become dynamic platforms for cultural communication and collective identity. This research contributes to the discourse on cultural resilience and offers insights for future studies on heritage preservation in the social sciences and humanities.